Cerebrovascular reactivity assessed by transcranial Doppler ultrasound in sport-related concussion: a systematic review. Issue 16 (1st December 2014) - Gardner, Andrew J; Tan, Can Ozan; Ainslie, Philip N; van Donkelaar, Paul; Stanwell, Peter; Levi, Christopher R; Iverson, Grant L
Abstract : Background: Traumatic brain injury influences regulation of cerebral blood flow in animal models and in human studies. We reviewed the use of transcranial Doppler ultrasound (US) to monitor cerebrovascular reactivity following sport-related concussion. Review method: A narrative and systematic review of articles published in the English language, from December 1982 to October 2013. Data sources: Articles were retrieved via numerous databases using relevant key terms. Observational, cohort, correlational, cross-sectional and longitudinal studies were included. Results: Three publications met the criteria for inclusion; these provided data from 42 athletes and 33 controls. All three studies reported reductions in cerebrovascular reactivity via transcranial Doppler US. Conclusions: These initial results support the use of cerebrovascular reactivity as a research tool for identifying altered neurophysiology and monitoring recovery in adult athletes. Larger cross-sectional, prospective and longitudinal studies are required to understand the sensitivity and prognostic value of cerebrovascular reactivity in sport-related concussion.